Studies of Interaction of Iron(II) Complexes with Human Serum Albumin by Spectrophotometric and Dialysis Equilibrium Methods - Singh, R.P.; Kumar, Rahul; Kumar Baliyan, Praveen (Asian Journal of Chemistry, 2010)
In this paper, we are studying about the complex formation between a metal, macromolecule and simple organic ligand have been investigated for different reasons. It is enable to determine the presence of chelating group in the vicinal positions for determining enzyme activity and explaining the drug mechanism.